A conceptual analysis of SBIRT implementation alongside the continuum of PrEP awareness: domains of fit and feasibility - Harris, Lesley M.; Kerr, Jelani C.; Skidmore, Blake D.; Ghare, Smita; Reyes-Vega, Andrea; Remenik-Zarauz, Vania; Samanapally, Harideep; Anwar, Rana Usman; Rijal, Rishikesh; Bryant, Kendall; Hall, Martin T.; Barve, Shirish (Frontiers in Public Health, 2024)
Screening, Brief Intervention, and Referral to Treatment (SBIRT) is a supplementary intervention that can be incorporated into the Pre-Exposure Prophylaxis (PrEP) Care Continuum, complementing initiatives and endeavors focused on Human Immunodeficiency Virus (HIV) prevention in clinical care and community-based work. Referencing the Transtheoretical Model of Change and the PrEP Awareness Continuum, this conceptual analysis highlights how SBIRT amplifies ongoing HIV prevention initiatives and presents a distinct chance to address identified gaps. SBIRT's mechanisms show promise of fit and feasibility through (a) implementing universal Screening (S), (b) administering a Brief Intervention (BI) grounded in motivational interviewing aimed at assisting individuals in recognizing the significance of PrEP in their lives, (c) providing an affirming and supportive Referral to Treatment (RT) to access clinical PrEP care, and (d) employing client-centered and destigmatized approaches. SBIRT is uniquely positioned to help address the complex challenges facing PrEP awareness and initiation efforts. Adapting the SBIRT model to integrate and amplify HIV prevention efforts merits further examination.